Some observations on the current state of bioethics in Argentina - Outomuro, Delia (Acta Bioethica, 2003)
This paper proposes as thesis that in Argentina bioethics runs the risk of operating as an institution in the anthropological sense this term and that, as such, far from contributing to the crystallisation of the emancipatory rationality, it performs the function of legitimating the statu quo. In Argentina, the three bioethic stages (the emotive, the reconstructive and the consolidation stage) coexist, with all the inherent dangers to each one of them. The legalism and the lawfulness of the ethical conflicts, the fundamentalism, the cheaters, the expert-cracy and the snobbism adulterate its real purpose of democratic coexistence. Finally, it is postulated that bioethics should promote the realisation of the ideal community of communication and that, therefore, the pluralistic, transdisciplinary and procedural character should prevail in this speech like a sine qua non condition for the articulation of people's emancipatory interests.